Culture Learning Management Al-Quran Model Tilawati to Improve Student Character - Umar Jaeni; Ismet Basuki; Moedjiarto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
This study aims to determine the culture of learning, management functions, and the learning process of the Quran with the Tilawati model, as well as to determine the character development by learning the Quran with the Tilawati model at Junior High School Al Muslim of Sidoarjo, Islamic Junior High School of 1 Surabaya and Junior High School of 34 Surabaya. This study used a multi-case study research method with a purposive sampling technique with the research subjects, namely 3 schools. The collection is done by giving questions related to culture, learning management, and the learning process in the three schools. From the research it can be concluded that 1) The culture of learning Al-Quran with the Tilawati model provides a fairly good contribution to fostering student character, 2) The use of management science principles in the implementation of the Tilawati model of Al Quran learning program is very appropriate, 3) The learning process of the Al-Quran model consists of interrelated components, including; graduation targets about quality and quantity, curriculum, management of learning Al-Quran with the Tilawati model, 4) To foster 25 student characters through learning the Tilawati Al-Quran model is done by designing learning with syntax or learning stages that are systematically arranged. This research implies that it can be used as material to improve the implementation of the Al-Quran learning culture by developing modern learning management principles.